Oligoclonal M bands and cervical spinal cord lesions predict early secondary progressive multiple sclerosis - Alcalá Vicente, Carmen; Lacruz, Laura; Gascón, Francisco; Carratalà, Sara; Quintanilla-Bordás, Carlos; Sanz, Maria T.; Carcelén-Gadea, María; Mallada, Javier; Carreres, Joan; Gabaldón Torres, Laura; Dominguez, Jose Andres; Cañizares, Emmanuel; et al. (Frontiers in Neurology, 2022)
Objective To determine baseline cerebrospinal fluid and magnetic resonance imaging (MRI) variables at the onset of a clinically isolated syndrome (CIS) suggestive of multiple sclerosis (MS) that predict evolution to secondary progressive MS (SPMS). Methods 276 CIS patients with a minimum follow-up of 10 years were studied. Baseline presence of oligoclonal IgG and IgM bands (OCGB and OCMB respectively); number of brain T2 lesions (B-T2L), brain gadolinium enhancement lesions (brain-GEL), cervical spinal cord T2 lesions (cSC-T2L); and fulfillment of 2017 McDonald criteria among other variables were collected. Results 14 patients ended up with a non-MS condition. 138/276 CIS patients fulfilled 2017 McDonald criteria. Mean age was 32.4 years, 185 female. 227 received treatment, 95 as CIS. After a mean follow-up of 12 years, 36 patients developed SPMS. Conversion to SPMS was associated with OCGB (p = 0.02), OCMB (p = 0.0001); ≥ 9 B-T2L (p = 0.03), brain-GEL (p = 0.03), and cSC-T2L (p = 0.03). However, after adjusting for sex, age, BT2L, brain-GEL, SC-T2, and OCMB status, only OCMB (HR 4.4, 1.9–10.6) and cSC-T2L (HR 2.2, 1.0–6.2) suggested an independent association with risk of conversion to SPMS. Patients with both risk factors had a HR of 6.12 (2.8–12.9). Discussion OCMB and SC-T2 lesions are potential independent predictors of conversion to SPMS.